Occupational Therapy for People Experiencing Illness, Injury or Impairment. Promoting Occupation and Participation, un manuel paru en 2017 sous la direction de Michael Curtin, Mary Egan et Jo Adams - Martine Brousseau (CARAFE - Communauté pour l'Avancement de la Recherche Appliquée Francophone en Ergothérapie, 2017)
Sans résumé.